Therapeutic efficacy and effects of artemisinin-based combination treatments on uncomplicated Plasmodium falciparum malaria -associated anaemia in Nigerian children during seven years of adoption as first-line treatments. Issue 1 (December 2017) - Sowunmi, Akintunde; Akano, Kazeem; Ntadom, Godwin; Ayede, Adejumoke; Ibironke, Folasade; Aderoyeje, Temitope; Adewoye, Elsie; Fatunmbi, Bayo; Oguche, Stephen; Okafor, Henrietta; Watila, Ismaila; Meremikwu, Martin; et al.
Abstract Background Artemisinin-based combination treatments (ACTs) are the first-line treatments of uncomplicatedPlasmodium falciparum malaria in many endemic areas but there are few evaluation of their efficacy in anaemic malarious children. Methods Therapeutic efficacy of 3-day regimens of artesunate-amodiaquine and artemether-lumefantrine was evaluated in 437 anaemic and 909 non-anaemic malarious children following treatment during a seven-year period (2008–2014). Patterns of temporal changes in haematocrit were classified based on haematocrit values <30% and ≥30%. Kinetics of the disposition of the deficit in haematocrit from 30% following treatment were evaluated using a non-compartment model. Results PCR-corrected parasitological efficacy 28 days after start of treatment was significantly higher in artesunate-amodiaquine- compared to artemether-lumefantrine-treated children [97% (95%CI : 92.8–100) versus 96.4% (95%CI : 91.3–99.4), P = 0.02], but it was similar in non-anaemic and anaemic children. Fall in haematocrit/1 000 asexual parasites cleared from peripheral blood was significantly greater at lower compared to higher parasitaemias (P < 0.0001), and in non-anaemic compared to anaemic children (P = 0.007). In anaemic children at presentation, mean anaemia recovery time (AnRT) was 15.4 days (95%CI : 13.3–17.4) and it did not change over the years. Declines in haematocrit deficits from 30% were monoexponential with mean estimated half-time of 1.4 days (95%CI : 1.2–1.6). Anaemia half-time (t½anaemia ) correlated positively with AnRT in the same patients (r = 0.69, P < 0.0001). Bland-Altman analysis of 10 multiples of t½anaemia and AnRT showed narrow limit of agreement with insignificant bias (P = 0.07) suggesting both can be used interchangeably in the same patients. Conclusions Artesunate-amodiaquine and artemether-lumefantrine remain efficacious treatments of uncomplicatedP. falciparum infections in non-anaemic and anaemic Nigerian children in the last 7 years of adoption as first-line treatments. These ACTs may also conserve haematocrit at high parasitaemias and in anaemic children. Trials registration Pan African Clinical Trial RegistryPACTR201508001188143, 3 July 2015;PACTR201510001189370, 3 July 2015;PACTR201508001191898, 7 July 2015 andPACTR201508001193368, 8 July 2015.